How Should We Think About Pharmaceutical Excipients in Clinical Pharmacy Education? - Han, Min; Jiang, Ruo-lin; Ying, Xiao-Ying; Gao, Jian-qing (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: As the pharmaceutical industry shifts to a patient-oriented approach, pharmaceutical education has fairly garnered increasing attention from educators, so that the teaching course centered on pharmaceutical excipients is becoming more and more popular. Purpose: The purpose of this study was to evaluate the significance of pharmaceutical excipients in clinical pharmaceutical education by a single-blind and parallel group design. Materials and Methods: The course was given in the form of small classes at Zhejiang University. The control group was taught in a traditional mode, while the intervention group mainly focused on the importance of pharmaceutical excipients in teaching. Likert five-point scale was used to analyze the test difficulty and learning effect of students in both groups. Results: Firstly, we investigated the test difficulty and learning time of the two groups of students, no significant difference was detectable between the two groups (p>0.05). Then, we investigated the learning effect of the two groups from four dimensions: accessibility of teachers’ teaching concept, inspiration of the teaching methods, independence of students in the teaching process, and the extent to which the curriculum expanded student’s horizons. It was found that the learning effect was much preferred in the intervention group as compared with the control group (p<0.05). Conclusion: The results showed that the emphasis on the integration of pharmaceutical excipients in pharmacy education had a positive impact on students' learning. Therefore, it is worth to reevaluate the role of pharmaceutical excipients in clinical pharmacy education.
Keywords: Clinical pharmacy education; Pharmaceutical excipients; Parallel group design; Teaching improvement